The relationship between obesity and nursing care problems in intensive care patients in Austria. - Großschädl, Franziska; Bauer, Silvia (Nursing in Critical Care, 2022)
Objectives: To describe the characteristics and nursing care problems of intensive care patients in Austria stratified by obesity. Background: Obese people in intensive care units (ICUs) present nurses with special challenges. Therefore, nurses need to receive education and training regarding how to treat obese patients to provide them with the best care. Most studies on obesity in ICU patients have not specifically addressed the problems and challenges from the nurses' perspective. This may be because nursing science programmes in Europe rarely introduce the topic of obesity. Design: This was a secondary data analysis of a longitudinal study. Methodology: The "Nursing Quality Measurement 2.0" is the Austrian version of the "International Prevalence Measurement of Care problems". It is an annual cross‐sectional study, which has been carried out since 2009. Data from all ICU patients for 2009 to 2018 were extracted and combined into one file (n = 460). The main outcome measures were obesity and various nursing care problems, including care dependency. Results: Of the ICU patients. 25% were obese. Obese ICU patients suffered significantly more often from diabetes mellitus and endocrine, nutritional, or metabolic diseases than non‐obese patients. About 30% of the ICU patients were totally care dependent, and 85.6% of the ICU patients were at risk of developing pressure ulcers, whereas the risk was higher for non‐obese than obese patients. ICU patients with a risk of pressure ulcer (measured with the Braden Scale) had a reduced risk of being obese (OR = 0.544). Conclusion: Overall, the prevalence of nursing care problems found in this study was high. No significant differences in the prevalence of nursing care problems between obese and non‐obese patients were found. However, because of the increase in the number of obese patients in all nursing settings, a stronger focus on obesity research in the area of nursing science is recommended.